Preparation method and application of composite catalytic material for reducing co2 to produce formic acid by light-enzyme cascade catalysis
Patent Information
- Application Number
- CN202611197253.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-10-27
AI Technical Summary
[0007]本发明的目的在于提供一种光-酶级联催化还原CO2产甲酸的复合催化材料及其制备方法,以解决现有技术中光催化单元光生电子-空穴对分离效率低、光吸收范围有限以及酶催化单元稳定性差、负载效率低的技术问题
本发明通过聚乙烯亚胺(PEI)对共价有机框架TPDQ进行改性,PEI分子中丰富的氨基官能团显著提升了材料的表面正电荷密度,增强了光催化单元与酶负载单元之间的静电吸附作用,同时PEI分子链穿插于材料孔隙中形成了高效的电子传输通道,显著提高了光生载流子的分离和传输效率,将NADH再生产率提升至未改性材料的2.5倍。
Smart Images

Figure CN122979292A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photocatalysis and enzyme catalysis, specifically relating to a composite catalytic material for the photo-enzyme cascade catalytic reduction of CO2 to formic acid and its preparation method, as well as the application of the composite catalytic material in the photo-enzyme cascade catalytic reduction of CO2 to formic acid. Background Technology
[0002] With the intensification of global climate change and the energy crisis, the efficient conversion and resource utilization of CO2 has become an important direction for scientific research. Traditional CO2 reduction methods, such as thermocatalysis and electrocatalysis, have made some progress, but still face problems such as high energy consumption, low selectivity, and poor catalyst stability. Photocatalysis, driven by solar energy, with mild reaction conditions and environmental friendliness, is considered one of the ideal pathways for CO2 reduction. However, single photocatalytic systems are often limited by bottlenecks such as the rapid recombination of photogenerated electron-hole pairs and low product selectivity.
[0003] While enzyme catalysis offers high efficiency, selectivity, and mild reaction conditions, its poor stability and reliance on expensive cofactors (NADH) limit its large-scale application. Therefore, designing a photo-enzyme cascade catalytic system that combines photocatalysis with enzyme catalysis can not only utilize the reducing power generated by photocatalysis to catalyze NAD+ reactions... + Regeneration drives enzyme-catalyzed reactions and enables the efficient conversion of CO2 into formic acid through the precise selectivity of enzymes.
[0004] Covalent organic frameworks (COFs) have shown great potential in photocatalysis due to their highly ordered pore structure, tunable chemical properties, and excellent photoelectric performance. However, COFs still suffer from problems such as rapid recombination of photogenerated electron-hole pairs and limited light absorption range. Researchers have proposed modification strategies such as morphology control, bandgap engineering, post-synthetic modification, and heterojunction engineering, but the improvement of photocatalytic performance by a single modification method is limited.
[0005] In addition, free enzymes suffer from drawbacks such as low thermal stability, narrow pH range, poor tolerance to harsh environments, and structural instability. Common enzyme immobilization methods include cross-linking, embedding, adsorption, and covalent binding, but single immobilization methods often have low loading efficiency and poor enzyme activity retention.
[0006] Therefore, there is an urgent need to develop a composite catalytic material that can simultaneously solve the two major bottleneck problems of low separation efficiency of photogenerated carriers in photocatalytic units and poor stability of enzyme catalytic units, so as to achieve efficient and stable photo-enzyme cascade catalytic reduction of CO2 to formic acid. Summary of the Invention
[0007] The purpose of this invention is to provide a composite catalytic material for the photo-enzyme cascade catalytic reduction of CO2 to formic acid and its preparation method, so as to solve the technical problems of low separation efficiency of photogenerated electron-hole pairs and limited light absorption range of photocatalytic units, as well as poor stability and low loading efficiency of enzyme catalytic units in the prior art.
[0008] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a method for preparing a composite catalytic material for the photo-enzyme cascade catalytic reduction of CO2 to formic acid, comprising the following steps: (1) Preparation of enzyme-loading unit SF N -FE: (1a) Preparation of silica nanoflowers SF: Hexadecyltrimethylammonium bromide and n-butanol were added to a round-bottom flask, urea solution was added, the mixture was heated and stirred in an oil bath, cyclohexane was added to form an emulsion, tetraethyl orthosilicate was added, the mixture was stirred and reacted in a water bath, cooled and washed with ethanol and water by centrifugation, dried and calcined in a muffle furnace to obtain silica nanoflowers SF; (1b) Preparation of amino-modified silica nanoflowers SF N The SF obtained in step (1a) and γ-aminopropyltriethoxysilane were added to a water-ethanol mixed solution, and the mixture was refluxed in an oil bath. The product was collected by centrifugation, washed, and dried to obtain amino-modified silica nanoflowers SF. N ; (1c) Loading formate dehydrogenase: The SF obtained in step (1b) is loaded with formate dehydrogenase. N Formate dehydrogenase was added to phosphate buffer, and the reaction was carried out under constant temperature and shaking. After centrifugation, washing, and freeze-drying, the enzyme-loaded unit SF was obtained. N -FE; (2) Preparation of photocatalytic unit TPDE: (2a) Preparation of covalent organic framework TPDQ: 1,3,5-trialdehyde phloroglucinol and 2,6-diaminoanthraquinone were added to a mixed solvent, ultrasonically dispersed, and then an aqueous acetic acid solution was added. After being frozen in liquid nitrogen and degassed by a freeze-evacuation-thaw cycle, the mixture was sealed and reacted under heating conditions. After washing and drying, covalent organic framework TPDQ was obtained. (2b) Polyethyleneimine modified TPDE: The TPDQ obtained in step (2a) was dispersed in deionized water, polyethyleneimine was added and stirred to react, centrifuged, washed and dried to obtain polyethyleneimine modified covalent organic framework TPDE; (3) Preparation of composite catalyst TPDE / SF N -FE: The SF obtained in step (1c) N-FE and TPDE obtained in step (2b) were added to phosphate buffer, stirred and mixed, followed by the addition of polyethyleneimine and continued stirring. After centrifugation, washing, and freeze-drying, the composite catalyst TPDE / SF was obtained. N -FE.
[0009] Preferably, in step (1a), the ratio of hexadecyltrimethylammonium bromide to n-butanol is 1g:(1.0-1.5)mL; the concentration of the urea solution is 0.3-0.5M; the amount of tetraethyl orthosilicate added is 2.0-2.5mL; the water bath reaction temperature is 60-80℃, and the reaction time is 16-24 hours; the calcination temperature is 500-600℃, and the calcination time is 4-6 hours.
[0010] Preferably, in step (1b), the mass-to-volume ratio of SF to γ-aminopropyltriethoxysilane is 1 g: (0.8-1.2) mL; the volume ratio of water to ethanol in the water-ethanol mixed solution is 1: (8-10); the reflux reaction temperature is 70-90℃, and the reaction time is 10-14 hours.
[0011] Preferably, in step (1c), the SF N The mass ratio of formate dehydrogenase to formate dehydrogenase is (1.5-2.5):1; the isothermal oscillation reaction temperature is 20-30℃, and the reaction time is 2-4 hours.
[0012] Preferably, in step (2a), the molar ratio of 1,3,5-trialdehyde phloroglucinol to 2,6-diaminoanthraquinone is (0.8-1.2):1; the mixed solvent is a mixture of mesitylene and 1,4-dioxane in a volume ratio of (0.8-1.2):1; the concentration of the acetic acid aqueous solution is 4-8M; the heating reaction temperature is 110-130℃, and the reaction time is 60-84 hours.
[0013] Preferably, in step (2b), the mass-to-volume ratio of TPDQ to polyethyleneimine is (1-2) mg:1 mL; and the stirring reaction time is 1-3 hours.
[0014] Preferably, in step (3), the TPDE and SF N The mass ratio of -FE is (1.5-2.5):1; the pH of the phosphate buffer is 6.8-7.4; and the stirring reaction time is 0.5-1.5 hours.
[0015] Secondly, the present invention provides a composite catalytic material for photo-enzyme cascade catalytic reduction of CO2 to formic acid prepared by the above preparation method.
[0016] Thirdly, the present invention provides the application of the above-mentioned composite catalytic material in the photo-enzyme cascade catalytic reduction of CO2 to formic acid.
[0017] Preferably, the application includes: combining the composite catalytic material with NAD. + NaHCO3 and rhodium complex [Cp*Rh(bpy)H2O] 2+ The mixture is mixed in phosphate buffer and subjected to a photo-enzyme cascade catalytic reaction under visible light with a wavelength of 420 nm to reduce CO2 to formic acid.
[0018] The beneficial effects of this invention are as follows: This invention modifies the covalent organic framework TPDQ with polyethyleneimine (PEI). The abundant amino functional groups in the PEI molecule significantly increase the surface positive charge density of the material, enhance the electrostatic adsorption between the photocatalytic unit and the enzyme loading unit, and at the same time, the PEI molecular chains interpenetrate in the pores of the material to form efficient electron transport channels, which significantly improves the separation and transport efficiency of photogenerated carriers and increases the NADH regeneration rate to 2.5 times that of the unmodified material.
[0019] This invention modifies silica nanoflowers with γ-aminopropyltriethoxysilane (APTES), increasing the number of amino groups on the material surface and providing more binding sites for formate dehydrogenase (FDH). The enzyme is efficiently loaded through covalent bonding between amino groups and carboxyl groups in FDH, as well as electrostatic adsorption. The FDH loading capacity is increased from 376 mg / g to 428 mg / g, and the loading concentration is increased from 75% to 85%.
[0020] This invention integrates the photocatalytic unit TPDE and the enzyme loading unit SF through electrostatic self-assembly. N The integration of -FE significantly shortens the transmission distance of photogenerated electrons from the photocatalyst to the enzyme, forming a highly efficient electron transport channel from the photocatalyst to the FDH loading unit. The composite material is negatively charged overall, enhancing NAD. + Enrichment and reduction around the composite material resulted in a formic acid contribution of 39.78 mmol / g per unit of FDH. FDH -1 It is 6.4 times that of the standalone system, with a formic acid yield of 5580 μmol·g. -1 ·h -1 It is significantly superior to existing technologies.
[0021] The unique petal-like structure of the silica nanoflowers and the sparser boundaries after APTES modification allow FDH to be loaded into a deeper internal structure. The covalent binding of amino functional groups to FDH further stabilizes the enzyme loading, providing a good microenvironment for FDH. The enzyme activity remains 7.7 times that of the free enzyme, which is significantly better than existing enzyme immobilization technologies.
[0022] This invention, through a rotating disk electrode experiment, is the first to verify that electrons preferentially participate in NAD in a photo-enzyme competitive reaction. + The reduction-mediated enzymatic reaction pathway provides new insights into the mechanism of photo-enzyme cascade catalytic reactions.
[0023] The composite catalytic material described in this invention has good cycle stability; after five cycles, the formic acid yield remains above 74%. Attached Figure Description
[0024] Figure 1 SF and SF in Embodiment 1 of the present invention N and SF N -Scanning electron microscope and transmission electron microscope images of FE; Figure 2 TPDQ, TPDE, SF, and SF in Embodiment 1 of the present invention N and SF N -FE X-ray diffraction pattern; Figure 3 The N2 adsorption-desorption isotherms and pore size distribution curves of TPDQ and TPDE in Example 1 of this invention are shown. Figure 4 TPDQ, TPDE, and TPDE / SF in Embodiment 1 of the present invention N -Scanning electron microscope and transmission electron microscope images of FE; Figure 5 SF-FE and SF in Embodiment 1 of the present invention N Comparison of UV-Vis absorption spectrum of FE, FDH loading concentration ratio and FDH loading amount; Figure 6 The graph shows the yield of different photocatalysts for NADH regeneration over time and the average yield value. Figure 7 This is a comparison chart of formic acid production under different addition methods in Example 1 of the present invention; Figure 8 The graphs show the formic acid yield, TOF value comparison, and TPDE / SF ratio of different materials in Example 1 of this invention. N -FE cycle formic acid production diagram; Figure 9 This is a diagram showing the formic acid production in the light-dark cycle reaction of Example 1 of the present invention. Detailed Implementation
[0025] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0026] Example 1
[0027] This embodiment proposes a composite catalytic material TPDE / SF for the photo-enzyme cascade catalytic reduction of CO2 to formic acid. N -FE, which is prepared by the following method: (1) Preparation of enzyme-loading unit SF N -FE: (1a) Preparation of silica nanoflowers SF: 1 g of hexadecyltrimethylammonium bromide (CTAB) and 1.23 mL of n-butanol were added to a 100 mL round-bottom flask, followed by 30 mL of urea solution (0.4 M). The mixture was heated and stirred in an oil bath at 25 °C for 5 minutes. After thorough mixing, 15.38 mL of cyclohexane was slowly added along the flask wall to form a homogeneous emulsion. Then, 2.14 mL of tetraethyl orthosilicate (TEOS) was slowly added dropwise using a dropper. The mixture was placed in a water bath at 70 °C and the reaction was continued with stirring for 20 hours. After cooling, the mixture was washed five times by centrifugation with ethanol and water, and the precipitate was collected. The resulting solid was dried in a vacuum drying oven at 70 °C for 8 hours, and then calcined in a muffle furnace at 550 °C with air as the medium for 5 hours. After cooling, the white solid powder was collected and thoroughly ground to obtain SF.
[0028] (1b) Preparation of amino-modified silica nanoflowers SF N : 1 g of SF and 1 mL of γ-aminopropyltriethoxysilane (APTES) were added to 100 mL of a water-ethanol mixture (water to ethanol volume ratio 1:9). The mixture was refluxed in an 80°C oil bath for 12 hours with stirring at 800 rpm. After the reaction was complete, the white precipitate was collected by centrifugation and washed three times with ethanol. The washed product was dried in a vacuum drying oven at 70°C for 12 hours to obtain a white solid, which was then ground into powder to obtain SF. N .
[0029] (1c) Loaded with formate dehydrogenase: 10mg SF N Add 5 mg of formate dehydrogenase (FDH) to 2 mL of PBS buffer and incubate at 25°C with a water bath shaker for 3 hours. After the reaction, wash the product three times with PBS buffer by centrifugation. Freeze-dry the product for 24 hours and store it at -20°C to obtain SF.N -FE.
[0030] (2) Preparation of photocatalytic unit TPDE: (2a) Preparation of covalent organic framework TPDQ: Accurately weigh 0.3 mmol (50.4 mg) of 1,3,5-trialdehyde phloroglucinol (TP) and 0.36 mmol (85.6 mg) of 2,6-diaminoanthraquinone (2,6-DAAQ), add them to a 25 mL hydrothermal reactor, add 15 mL of mixed solvent (trimethylbenzene and 1,4-dioxane mixed at a volume ratio of 1:1), and sonicate to achieve uniform dispersion. Quickly add 2.5 mL of 6 M acetic acid aqueous solution, and sonicate again to achieve uniform dispersion. Rapidly freeze the hydrothermal reactor to 77 K using liquid nitrogen, and degas through three freeze-thaw cycles. Seal the hydrothermal reactor and heat the reaction at 120 °C for 72 hours. Wash the obtained solid five times with methanol until the supernatant is colorless and transparent, dry it in a vacuum drying oven at 70 °C for 8 hours, and grind it to obtain red powder TPDQ.
[0031] (2b) Polyethyleneimine modified TPDE: Dissolve 20 mg of TPDQ in 20 mL of deionized water, add 1 mL of polyethyleneimine (PEI), and stir at 800 rpm for 2 hours. After the reaction, centrifuge and wash several times with deionized water until the supernatant is neutral, dry in a vacuum drying oven at 70 °C for 8 hours, and grind into powder to obtain TPDE.
[0032] (3) Preparation of composite catalyst TPDE / SF N -FE: Accurately weigh 20 mg TPDE and 10 mg SF. N -FE were added to 20 mL of PBS buffer and stirred continuously at 800 rpm for 5 minutes. Then, 200 mL of PEI was added, and the mixture was stirred for 1 hour. After the reaction was complete, the precipitate was washed three times with PBS buffer by centrifugation until the supernatant was clear and colorless. The collected solid material was freeze-dried for 24 hours to obtain TPDE / SF. N -FE.
[0033] Example 2
[0034] This embodiment proposes a composite catalytic material TPDE / SF for the photo-enzyme cascade catalytic reduction of CO2 to formic acid. N -FE, whose preparation method is basically the same as that in Example 1, with the only difference being: In step (1a), the amount of tetraethyl orthosilicate added is 2.0 mL, the water bath reaction temperature is 60 °C, and the reaction time is 24 hours.
[0035] In step (2a), the molar ratio of 1,3,5-trialdehyde phloroglucinol to 2,6-diaminoanthraquinone is 1:1, the heating temperature is 110°C, and the reaction time is 84 hours.
[0036] Example 3
[0037] This embodiment proposes a composite catalytic material TPDE / SF for the photo-enzyme cascade catalytic reduction of CO2 to formic acid. N -FE, whose preparation method is basically the same as that in Example 1, with the only difference being: In step (1a), the amount of tetraethyl orthosilicate added is 2.5 mL, the water bath reaction temperature is 80 °C, and the reaction time is 16 hours.
[0038] In step (2a), the molar ratio of 1,3,5-trialdehyde phloroglucinol to 2,6-diaminoanthraquinone is 0.8:1, the heating temperature is 130°C, and the reaction time is 60 hours.
[0039] Comparative Example 1 This comparative example presents a composite catalytic material, the preparation method of which is basically the same as that in Example 1, except that step (2b) is omitted, that is, TPDQ is not modified with PEI, and TPDQ is directly used as a photocatalytic unit with SF6. N -FE composite yields TPDQ / SF N -FE.
[0040] Comparative Example 2 This comparative example proposes a composite catalytic material, the preparation method of which is basically the same as that of Example 1, except that step (1b) is omitted, that is, SF is not modified by APTES, and SF-FE is obtained by directly loading FDH with SF, and then combined with TPDE to obtain TPDE / SF-FE.
[0041] Comparative Example 3 This comparative example presents a composite catalytic material, the preparation method of which is basically the same as that of Example 1, the only difference being: the addition of PEI in step (3) is omitted, i.e., TPDE and SF N -FE is compounded only through simple mixing rather than electrostatic assembly.
[0042] Figure 1 SF and SF prepared in Example 1 N SF N -FE scanning electron microscope and transmission electron microscope images. The results show that SF exhibits a regular spherical structure with petal-like nanostructures inside; APTES-modified SF N The internal structure is more compact, the petal-like boundaries are clearer, and the size is slightly larger; after loading FDH, SF NThe petal-shaped boundary around FE is darkened, indicating that FDH was successfully loaded onto SF. N surface.
[0043] Figure 2 SF and SF prepared in Example 1 N SF N X-ray diffraction patterns of FE, TPDQ, and TPDE were obtained. The results showed that SF exhibited a broad, diffuse peak near 23°, characteristic of the amorphous form of silica; APTES-modified SF... N and SF N -FE exhibits similar characteristics at the same angle. TPDQ shows obvious characteristic diffraction peaks near 1.2° and 27.4°, exhibiting an AA stacked structure; PEI-modified TPDE shows similar characteristic peaks, proving that PEI modification did not destroy the crystal structure of TPDQ.
[0044] Figure 3 The N2 adsorption-desorption isotherms and pore size distribution curves of TPDQ and TPDE prepared in Example 1 are shown. The results show that both TPDQ and TPDE exhibit typical type IV isotherms, indicating that both possess a composite structure of mesoporous and microporous structures. The specific surface area of the PEI-modified material increased from 200 m² / m³. 2 / g decreased to 52m 2 / g, the average pore size increased from 15nm to 34nm, proving that PEI was successfully modified into the TPDQ channels.
[0045] Figure 4 TPDQ, TPDE, and TPDE / SF prepared in Example 1 N -FE scanning electron microscope and transmission electron microscope images. The results show that TPDQ exhibits a three-dimensional porous coral-like structure formed by the self-assembly of nanowires; PEI-modified TPDE basically maintains the coral-like framework structure, and the nanowire surface becomes smoother and flatter; TPDE / SF N -FE composite materials, while maintaining a coral-like structure, have a large number of spherical nanoparticles uniformly distributed on their surface, proving that SF N -FE was successfully loaded onto the TPDE surface.
[0046] Figure 5 SF-FE and SF in Example 1 N Comparison of UV-Vis absorption spectra of FE, FDH loading concentration ratio, and FDH loading amount. SF N The FDH loading concentration in the system was increased from 75% to 85%, and the FDH loading amount increased from 376 mg / g to 428 mg / g, demonstrating that APTES modification significantly improved the FDH loading capacity of SF.
[0047] In this invention, to demonstrate the application of the composite catalytic material in the photocatalytic regeneration of NADH, the composite catalytic material (or the corresponding photocatalytic unit) described in the examples and comparative examples is used as a photocatalyst to regenerate oxidized coenzyme NAD. + To obtain reduced coenzyme NADH: Configure 20mM NAD + Aqueous mother liquor and 20 mM rhodium complex ([Cp*Rh(bpy)H2O]) 2+ The test was conducted at room temperature using a PBS buffer (100 mM) at pH 7.2. The application test of photocatalytic regeneration of NADH specifically included adding 20 mg of NAD+ to a double-layered, circulating water photoreactor. + The following ingredients were added: 3 mg of the composite catalytic material (or corresponding photocatalytic unit) described in the examples or comparative examples; 0.5 mL of a 20 mM rhodium complex aqueous solution stock solution; and a sacrificial agent (0.5 mL ascorbic acid or 0.25 mL triethanolamine). PBS buffer was added to bring the total solution volume to 20 mL. A 300 W xenon lamp equipped with a 420 nm filter was used as the light source. The reaction was allowed to proceed in the dark for 30 minutes before illumination to reach adsorption-desorption equilibrium. Illumination was then initiated to begin the reaction. The reaction solution was sampled at regular intervals, filtered, and the absorbance of the system at 340 nm was measured using a UV-Vis spectrophotometer. The NADH yield was calculated based on the NADH standard curve.
[0048] Figure 6 The graphs show the yield changes over time and average yield values for NADH regeneration using different photocatalysts in Example 1. After 60 minutes of illumination, the NADH regeneration rate of TPDE is 2.5 times that of TPDQ. (TPDE / SF) N The NADH regeneration rate was slightly higher than that of TPDE, indicating that PEI modification significantly improved the photocatalytic NADH regeneration performance.
[0049] In this invention, the composite catalytic materials described in Examples 1-3 and Comparative Examples 1-3 are used for application testing in the photo-enzyme cascade catalytic reduction of CO2 to formic acid. Specific applications include: Weigh 20 mg of NAD +1.45 g of NaHCO3 was added to a double-layered photoreactor with circulating water. The circulating water system was turned on and heated to 50°C. 20 mL of PBS buffer was added and stirred until homogeneous. 3 mg of composite catalyst was weighed and added, and stirred until homogeneous. Sacrificial agent (0.5 mL AA or 0.25 mL TEOA) and 0.5 mL Mbpy (20 mM) were added. Adsorption was carried out in the dark for 30 minutes, while the xenon lamp was turned on and preheated with a 420 nm filter for 30 minutes. After the dark reaction was completed, the reaction system was placed under light to start the reaction. Samples were taken every 30 minutes, filtered, and placed in liquid chromatography vials. The products were detected by high performance liquid chromatography (HPLC). The HPLC detection conditions were as follows: Hi-Plex H column (300nm×7.7nm), detection wavelength 220nm, column temperature 50℃, mobile phase 5mM H2SO4 solution, flow rate 0.6mL / min, injection volume 10μL, and run time 20min. The formic acid content was calculated based on the formic acid standard curve.
[0050] Figure 7 This is a comparison chart of formic acid yields under different dosing methods in Example 1. TPDE / SF N The formic acid yield of the -FE composite system was significantly higher than that of the single-addition system, with the formic acid contribution per unit FDH reaching 39.78 mmol / g after 3 hours of reaction. FDH -1 It is 6.4 times that of a standalone system.
[0051] Figure 8 The graphs show the formic acid yield, TOF value comparison, and TPDE / SF ratio of different materials in Example 1. N - FE cycle formic acid production diagram. TPDE / SF N The formic acid yield and TOF value of the -FE system are significantly higher than those of other systems. After five cycles of reaction, the performance of the composite material still remains above 74%, indicating that it has good cycle stability.
[0052] Figure 9 This is a graph showing the formic acid yield in the light-dark cycle reaction of Example 1. TPDE / SF N The formic acid formation rate in the -FE system was significantly higher than that in the enzyme-free control group, confirming a highly efficient synergistic effect between the FDH-supported unit and the photocatalyst TPDE. The formic acid formation rate under illumination was significantly higher than under darkness, but the formic acid yield still increased over time under darkness, indicating that the enzymatic reaction continues to play a crucial role throughout the catalytic process.
Claims
1. A method for preparing a composite catalytic material for the photo-enzyme cascade catalytic reduction of CO2 to formic acid, characterized in that, Includes the following steps: (1) Preparation of enzyme-loading unit SF N -FE: (1a) Preparation of silica nanoflowers SF: Hexadecyltrimethylammonium bromide and n-butanol were added to a round-bottom flask, urea solution was added, the mixture was heated and stirred in an oil bath, cyclohexane was added to form an emulsion, tetraethyl orthosilicate was added, the mixture was stirred and reacted in a water bath, cooled and washed with ethanol and water by centrifugation, dried and calcined in a muffle furnace to obtain silica nanoflowers SF; (1b) Preparation of amino-modified silica nanoflowers SF N The SF obtained in step (1a) and γ-aminopropyltriethoxysilane were added to a water-ethanol mixed solution, and the mixture was refluxed in an oil bath. The product was collected by centrifugation, washed, and dried to obtain amino-modified silica nanoflowers SF. N ; (1c) Loading formate dehydrogenase: The SF obtained in step (1b) is loaded with formate dehydrogenase. N Formate dehydrogenase was added to phosphate buffer, and the reaction was carried out under constant temperature and shaking. After centrifugation, washing, and freeze-drying, the enzyme-loaded unit SF was obtained. N -FE; (2) Preparation of photocatalytic unit TPDE: (2a) Preparation of covalent organic framework TPDQ: 1,3,5-trialdehyde phloroglucinol and 2,6-diaminoanthraquinone were added to a mixed solvent, ultrasonically dispersed, and then an aqueous acetic acid solution was added. After being frozen in liquid nitrogen and degassed by a freeze-evacuation-thaw cycle, the mixture was sealed and reacted under heating conditions. After washing and drying, covalent organic framework TPDQ was obtained. (2b) Polyethyleneimine modified TPDE: The TPDQ obtained in step (2a) was dispersed in deionized water, polyethyleneimine was added and stirred to react, centrifuged, washed and dried to obtain polyethyleneimine modified covalent organic framework TPDE; (3) Preparation of composite catalyst TPDE / SF N -FE: The SF obtained in step (1c) N -FE and TPDE obtained in step (2b) were added to phosphate buffer, stirred and mixed, followed by the addition of polyethyleneimine and continued stirring. After centrifugation, washing, and freeze-drying, the composite catalyst TPDE / SF was obtained. N -FE.
2. The preparation method according to claim 1, characterized in that, In step (1a), the ratio of hexadecyltrimethylammonium bromide to n-butanol is 1 g: (1.0~1.5) mL; the concentration of the urea solution is 0.3~0.5 M; the amount of tetraethyl orthosilicate added is 2.0~2.5 mL; the water bath reaction temperature is 60~80℃, and the reaction time is 16~24 hours; the calcination temperature is 500~600℃, and the calcination time is 4~6 hours.
3. The preparation method according to claim 1 or 2, characterized in that, In step (1b), the mass-to-volume ratio of SF to γ-aminopropyltriethoxysilane is 1 g: (0.8~1.2) mL; the volume ratio of water to ethanol in the water-ethanol mixed solution is 1: (8~10); the reflux reaction temperature is 70~90℃, and the reaction time is 10~14 hours.
4. The preparation method according to any one of claims 1 to 3, characterized in that, In step (1c), the SF N The mass ratio of formate dehydrogenase to formate is (1.5~2.5):1; the isothermal oscillation reaction temperature is 20~30℃, and the reaction time is 2~4 hours.
5. The preparation method according to any one of claims 1 to 4, characterized in that, In step (2a), the molar ratio of 1,3,5-trialdehyde phloroglucinol to 2,6-diaminoanthraquinone is (0.8~1.2):1; the mixed solvent is a mixture of mesitylene and 1,4-dioxane in a volume ratio of (0.8~1.2):1; the concentration of the acetic acid aqueous solution is 4~8M; the heating reaction temperature is 110~130℃, and the reaction time is 60~84 hours.
6. The preparation method according to any one of claims 1 to 5, characterized in that, In step (2b), the mass-to-volume ratio of TPDQ to polyethyleneimine is (1~2) mg:1 mL; the stirring reaction time is 1~3 hours.
7. The preparation method according to any one of claims 1 to 6, characterized in that, In step (3), the TPDE and SF N The mass ratio of -FE is (1.5~2.5):1; the pH of the phosphate buffer is 6.8~7.4; and the stirring reaction time is 0.5~1.5 hours.
8. A composite catalytic material for the photo-enzyme cascade catalytic reduction of CO2 to formic acid, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 7.
9. The application of the composite catalytic material of claim 8 in the photo-enzyme cascade catalytic reduction of CO2 to formic acid.
10. The application according to claim 9, characterized in that, The application includes: combining the composite catalytic material with NAD. + NaHCO3 and rhodium complex [Cp*Rh(bpy)H2O] 2+ The mixture is mixed in phosphate buffer and subjected to a photo-enzyme cascade catalytic reaction under visible light with a wavelength of 420 nm to reduce CO2 to formic acid.